Application of biometric models of authentication in mobile equipment. Issue 25 (2019) - Abazi, Blerton; Qehaja, Besnik; Hajrizi, Edmond
Abstract: Today's mobile devices are the most common investment in the technology industry as it is almost impossible to find a person who does not own a personal phone. Being the weakest point of nearly every user, as the data stored in it is essential, increased phone access security has been achieved by using biometric authentication modalities on these mobile devices. Here, the biometric modules that are most commonly used for authentication and how they are shared, the process of access and the weaknesses of each of these biometric modalities will be elaborated. Also indicate what are the potential attacks and problems that can be encountered in each of the biometric authentication methods on mobile devices.